2019
DOI: 10.1038/s41567-019-0695-1
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a ferro-rotational order coupled with second-order nonlinear optical fields

Abstract: The ferro-rotational order 1-3 , whose order parameter (OP) is an axial vector invariant under both time reversal (TR) and spatial inversion (SI) operations, is the last remaining category of ferroics to be observed after the ferroelectric, ferromagnetic, and ferro-toroidal orders. This order has become increasingly popular in many new quantum materials, especially in complex oxides 1,3 , and is considered responsible for a number of novel phenomena such as polar vortices 4 , giant magnetoelectric coupling 5 ,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 34 publications
(36 reference statements)
3
58
0
Order By: Relevance
“…Furthermore, the length scales of the ferroaxial domains observed in NiTiO 3 are on the orders of 10 0 ~ 10 2 μm. Such length scales are roughly comparable with the result of a previous SHG study which reported uneven domain populations in ferroaxial RbFe(MoO 4 ) 2 obtained from measurements using incident light with a 50-μm diameter spot on the sample 8 .…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, the length scales of the ferroaxial domains observed in NiTiO 3 are on the orders of 10 0 ~ 10 2 μm. Such length scales are roughly comparable with the result of a previous SHG study which reported uneven domain populations in ferroaxial RbFe(MoO 4 ) 2 obtained from measurements using incident light with a 50-μm diameter spot on the sample 8 .…”
Section: Resultssupporting
confidence: 88%
“…Besides conventional ferroic materials such as ferromagnetics, vector-like forms of ferroic orders, for example, ferro-toroidal order, attract much interests in the past decades 3 , 26 , 27 . Furthermore, the recent observation of ferroaxial (or ferro-rotational) order in displacive type RbFe(MoO 4 ) 2 using rotational anisotropy SHG 8 has added another ferroic ordered state with vector-like order parameters. The present study reveals spatial distributions of ferroaxial domains in NiTiO 3 on both nanometer and micrometer scales by means of STEM-CBED and linear optical microscopy using the EG effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional probes of symmetry rely on diffractive techniques, like x-ray, neutron, and electron scattering, to determine the respective lattice, magnetic, and charge ordering in a crystal. Nonlinear optics is also an effective probe of symmetry, as the nonlinear response is described by a third (or higher) rank tensor [5,6], allowing for phases hidden to linear probes (e.g., in correlated electron systems) to be revealed [27][28][29][30]. In the transition metal monopnictide (TMMP) family of WSMs, the lack of inversion symmetry resulting from a polar c-axis leads to an especially strong nonlinear optical response, with significant contributions from the generation of helicity-dependent injection [31][32][33] and helicityindependent shift [32,[34][35][36] photocurrents.…”
Section: Introductionmentioning
confidence: 99%